Sigmoido-vesical fistula secondary to sigmoid colon cancer presenting as urinary tract infection with Lactococcus lactis: A case report - An, Yanhua; Cao, Qiumei; Liu, Yixin; Lei, Luping; Wang, Dawei; Yang, Yanjie; Kong, Weijie; An, Dali; Liu, Dan (Frontiers in Oncology, 2023)
Colovesical fistula is a pathological communication between the colon and bladder. The symptoms include pneumaturia, fecaluria, and lower urinary tract infection. Urine cultures performed in patients with colovesical fistulas usually show growth of Escherichia coli or mixed growth of bowel organisms. Urinary tract infections caused by Lactococcus lactis are very rare, as it is rarely considered pathogenic in humans. We report the case of a 70-year-old woman who presented with symptoms of recurrent urinary tract infection. Clean mid-stream urine cultures were positive for L. lactis. The microbial identification was done by VITEK 2 compact system (Biomerieux Ltd., France). On admission, poor glycemic control was considered the probable cause of urinary tract infection, the initial treatments appeared effective. On the day 10 of admission, sudden worsening of symptoms were observed despite ongoing treatment, further work-up was then considered. Abdominopelvic computed tomography (CT) revealed focal thickening of the bladder wall and gas in the bladder. Cystoscopic examination and colonoscopy revealed sigmoid colon cancer and sigmoido-vesical fistula. Laparoscopic surgical treatment was done. The patient recovered and was discharged 3 week later without chemoradiotherapy. On follow-up after 6 months, the patient was asymptomatic and stable. To our knowledge, this is the second reported case of L. lactis infection of the urinary tract and the first reported case in adults. L. lactis infection usually indicates the presence of serious underlying diseases such as malignancies, uncontrolled diabetes, and organ failure.